PERAN DESA MANDIRI BENIH MENDUKUNG PERCEPATAN ADOPSI TEKNOLOGI VARIETAS UNGGUL BARU PADI - Resty Puspa Perdana; nFn Sunarsih; Adang Agustian; Chairul Muslim; Dewa K S Sadra; Achmad Suryana (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
Agricultural research and development agencies have produced several new improved rice varieties (NIRVs) over the past few years with various advantages to dealing with climate change and increasing rice production. However, until now, the adoption of NIRVs is still relatively low. This paper aims to determine the performance and problems of adopting NIRVs and recommend strategies for accelerating the adoption of NIRVs by increasing seed availability through the role of Seed Mandiri Village. This paper is the result of a review of several research results and relevant literature. Of the many NIRVs that have been released, until now, their distribution is still very limited. Most farmers still use improved rice varieties that have been released for a long time, such as Ciherang, Mekongga, and IR64. The low level of availability of NIRV seeds on a commercial scale is one of the inhibiting factors for the adoption and spread of NIRVs. Optimizing the role of the Seed Self-Reliant Village can increase the availability of NIRV seeds. Seed Self-Reliant Village in various regions can be encouraged to carry out sustainable breeding of NIRV seeds, especially for location-specific NIRV seeds. Thus, it is expected that these efforts will increase the adoption of NIRVs so that they can further have implications for increasing rice production and meeting national food needs.